P546 'STIs are everyone's responsibility': a new conceptual model of sexual health among gay and bisexual men. (14th July 2019) - Callander, Denton; Philpot, Steven; Mao, Limin; Mackie, Brent; Duck, Tim; Cooper, Craig; Vaughan, Matthew; Kao, Shih-Chi; Lewis, Larissa; Donovan, Basil; Bourne, Chris
Abstract : Background: Around the world, rates of sexually transmissible infections (STIs) continue to rise among gay and bisexual men. To respond to these increases, information is needed on the sociocultural realities underpinning prevention and management among at-risk populations, including gay and bisexual men. Methods: In mid-2018, qualitative data were collected from an Australian sample of gay men via a moderated online discussion forum (n=35) and in-depth interviews with forum participants (n=5) and sexual health physicians (n=4). An inductive thematic analysis was undertaken. Results: First, gay men and sexual health physicians mostly agreed that STIs should be a normalised, de-stigmatised aspect of sexuality. Second, many participants felt that STI prevention and management should be individualised, tailored to individual need and preference. Third, participants desired a holistic approach to sexual health that encompassed multiple, complementary strategies for managing sexual health. Participants characterised this conceptual model as the 'ideal', acknowledging that in reality and within each domain this vision is not always realised. For example, participants described stigmatising reactions to partner notification and condom use (or non-use). Physicians, on the other hand, reflected on the real-life limitations of providing individualised patient care, particularly the strain frequent testing and treatment places on resource-limited health settings. Finally, many participants felt that some strategies (notably HIV pre-exposure prophylaxis) were disproportionately valued by individuals and health organisations, undermining a holistic approach by focusing on one dominant strategy. Conclusion: The conceptual model defined by this research provides a framework for future efforts to promote sexual health while acknowledging enduring challenges to normalised, individualised and holistic approaches. Gay and bisexual men and sexual health physicians value a multifaceted and choice-driven approach to sexual health, reinforcing the need for a menu of prevention options that reflect the realities of STI transmission balanced against the resources required to deliver sexual health care. Disclosure: No significant relationships.